CRİMES BETWEEN 1880-1884 İN THE OTTOMAN SYRİA - Kürşat ÇELİK (Fırat University, 2019)
Crimes committed in the past are as of great significance as the characteristics and numbers of crimes. Discovery of data and information which will be answer to a certain number of historical and sociological questions will undoubtedly contribute to the men of science who study both history and sociology. To this end, both historians and the sociologists are to make interdisciplinary studies. This study has been conducted with this aim. This paper examines crimes commited during the years 1880-1884 in Damascus, Beirut, Tripoli, Latakia, Acre, Hamah, Belkâ (Nablus) and Havran, cities which are within the borders today’s Syria, Lebanon, Israel and Jordan, a region called the Syrian Province under the Ottoman sovereignty, according to records in annuals of Syrian province.